Cobalt Coordinated Cyano Covalent-Organic Framework for High-Performance Potassium-Organic Batteries - Zhao, Lu; Zheng, Lu; Li, Xiaopeng; Wang, Han; Lv, Li-Ping; Chen, Shuangqiang; Sun, Weiwei; Wang, Yong (ACS applied materials & interfaces, 2021)
Potassium ion batteries (PIBs) are expected to become the next large-scale energy storage candidates due to its low cost and abundant resources. And the covalent organic framework (COF), with designable periodic organic structure and ability to organize redox active groups predictably, has been considering as the promising organic electrode candidate for PIB. Herein, we report the facile synthesis of the cyano-COF with Co coordination via a facile microwave digestion reaction and its application in the high-energy potassium ion batteries for the first time. The obtained COF-Co material exhibits the enhanced π–π accumulation and abundant defects originated from the Co interaction with the two-dimensional layered sheet structure of COF, which are beneficial for its energy-storage application. Adopted as the inorganic-metal boosted organic electrode for PIBs, the COF-Co with Co coordination can promote the formation of the π–K+ interaction, which could lead to the activation of aromatic rings for potassium-ion storage. Besides, the porous two-dimensional layered structure of COF-Co with abundant defects can also promote the shortened diffusion distance of ion/electron with promoted K+ insertion/extraction ability. Enhanced cycling stability with large reversible capacity (371 mAh g–1 after 400 cycles at 100 mA g–1) and good rate properties (105 mAh g–1 at 2000 mA g–1) have been achieved for the COF-Co electrode.